Analisis Pengaruh Penambahan Jam Kerja (Lembur) dan Penambahan Tenaga Kerja Terhadap Keberhasilan Proyek - Nurfinasari RA Sanggu; Mohammad Yusuf Tuloli; Arfan Utiarahman (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the effect of additional working hours (overtime) and additional workforce on project success in the construction of the BPK RI Apartment Building in Gorontalo City. The independent variables examined in this study are additional working hours (X1) and additional workforce (X2), while the dependent variable is project success (Y). Data analysis was conducted using multiple linear regression to examine the relationship and influence among variables. The sample consisted of 41 respondents who were workers and project executors involved in the construction of the BPK RI Apartment Building in Gorontalo City. Data were collected through questionnaires that had been tested for validity and reliability. The results of these tests indicated that all research instruments were valid and reliable, and therefore suitable for use in this study. The results of the analysis indicate that additional working hours and additional workforce simultaneously have a significant effect on project success. This is supported by the F-test results, which show a significance value of 0.037, which is less than 0.05. Partially, the t-test results demonstrate that additional working hours (X1) have a significant effect on project success, with a significance value of 0.023 (< 0.05). Similarly, additional workforce (X2) also has a significant effect on project success, with a significance value of 0.037 (< 0.05). The coefficient of determination (R²) value of 0.399 indicates that the independent variables collectively explain 39.9% of the variation in project success. The remaining 60.1% is influenced by other factors not examined in this study.